Respuesta :
Answer:
The correct step that we need to do next in order to find the inverse of a function is:
D) Solve for y
Step-by-step explanation:
If we are given a function f(x) and we are asked to find it's inverse then first we put the function f(x)=y
Then we switch the places of x and y and finally we solve for y to find the required inverse function.
For example if we are given a function f(x) by:
[tex]f(x)=x+\dfrac{3}{2}[/tex]
Then we find the inverse as follows:
- Put [tex]f(x)=y[/tex]
i.e.
[tex]y=x+\dfrac{3}{2}[/tex]
- Next we switch the x and y value i.e.
[tex]x=y+\dfrac{3}{2}[/tex]
- Lastly we solve for y as follows:
We subtract both side by 3/2 to get:
[tex]y=x-\dfrac{3}{2}[/tex]
Hence, the inverse of function f(x) is:
[tex]g(x)=x-\dfrac{3}{2}[/tex]